Development of competency framework for postgraduate anesthesia training in China: a Delphi study - Xiaoning Zhang; Kun Meng; Junli Cao; Youhua Chen (BMC Medical Education)
Abstract Background Standardized postgraduate medical education (PGME) in anesthesiology is not well-defined in China. Establishing a competency framework for postgraduate anesthesia training (PGAT) is essential for standardizing and enhancing the quality of training and patient care. Objectives This study aimed to develop a competency framework for PGAT in China. Methods This study employed a multi-step approach, including a literature review, semi-structured interviews, to formulate a list of preliminary competencies. This initial list included seven roles, 26 enabling competencies, and 162 competency items. A modified Delphi method was utilized to achieve consensus involving three rounds. Experts were recruited from the Chinese Society of Anesthesiology (CSA) across various regions of the country. Consensus was determined using a 5-point Likert scale, with a mean score of ≥ 4 and a consensus rate of ≥ 80% serving as criteria for agreement. Results Forty-seven experts accepted the invitation to participate, with 46 returning scores for round 1 (90.2% response rate) and 45 returning scores for rounds 2 and 3 (88.2% response rate). The final competency framework includes 140 competency items within 23 enabling competencies, categorized into seven roles: medical expert, communicator, collaborator, professional leader, health advocate, academic scholar, and specialized professional. Conclusions This study represents an initial step towards establishing a contemporary competency-based medical education and training (CBMET) program for PGAT in China.